ANALISIS WACANA PEMBERITAAN PADA KOMPAS.ID TENTANG MEREVITALISASI BAHASA DAERAH SUMATERA SELATAN - Suhendra Suhendra (Jurnal Komunikasi dan Budaya, 2023)
This paper analyzes the news discourse in Kompas.id about revitalizing the regional language of South Sumatra. The study aims to explore how Kompas.id constructs news discourse about revitalizing the regional language of South Sumatra and how it represents the language and culture of South Sumatra in its coverage. The study uses a critical discourse analysis approach and focuses on three news articles published by Kompas.id between January and March 2023.The analysis reveals that Kompas.id constructs the news discourse about revitalizing the regional language of South Sumatra through several themes, including the importance of preserving the language and culture of South Sumatra, the government's efforts to promote and revitalize the regional language, and the challenges faced in revitalizing the language. The news articles highlight the importance of language in preserving cultural heritage and identity, and they emphasize the need to support and promote regional languages.The analysis also shows that Kompas.id represents the language and culture of South Sumatra in a positive and respectful manner. The news articles feature quotes from local language experts and community leaders, who express their support for the revitalization of the regional language. Kompas.id also highlights the efforts of the South Sumatra government to promote the language and culture of the region, including through the establishment of language centers and the inclusion of regional languages in the school curriculum.However, the analysis also reveals some limitations in Kompas.id's coverage of the revitalization of the regional language of South Sumatra. The news articles focus mainly on the government's efforts and initiatives to promote the language, and there is little discussion of the challenges faced by local communities in preserving and revitalizing their language. Moreover, the news articles do not provide a critical perspective on the government's policies and initiatives, which may have implications for the effectiveness of these efforts.In conclusion, Kompas.id constructs news discourse about revitalizing the regional language of South Sumatra through themes that emphasize the importance of preserving cultural heritage and identity, the government's role in promoting and revitalizing regional languages, and the challenges faced in this process. Kompas.id represents the language and culture of South Sumatra in a positive and respectful manner, but its coverage is limited in terms of providing a critical perspective on the government's policies and initiatives.